Clinical Laryngology. - Fried, Marvin P. (Thieme, 2014)
Clinical Laryngology addresses the practical issues faced by residents and seasoned practitioners in managing patients with diseases of the larynx. It is a concise manual covering common, everyday procedures that residents must master and provides all the up-to-date information needed by otolaryngologists caring for patients with laryngeal pathology. Key Features: Contains chapters on dysphagia, aspiration, tracheotomy, and cough Includes more than 100 high-quality illustrations and clinical photographs that clarify the information in the text Written and edited b.